Development and understanding of gymnastics skills using multi-body dynamics and computer simulation - Sheets, A. L.; Hubbard, M. (2003)
Computer simulation can be used to foster the development of gymnastics skills while reducing the training stress endured by the athlete. The creation of the model of the gymnast`s body and equipment requires a number of simplifying assumptions about the inertia and muscle properties of the athlete, and about the forces that the equipment exerts on the gymnast during execution. It also requires assumptions for initial conditions and muscular activation patterns during execution. Using the model to identify characteristics necessary for the positive outcome of a skill, and to identify maneuvers that are appropriate for the gymnast`s body type could reduce necessary training time and repetition while increasing the likelihood of consistent performance. Computer simulation could even facilitate the development of new skills.